Reductive cleavage of azo compounds with hydrazine hydrate and some new 1,3,4-thiadiazole derivatives - Rollas, Sevim (Marmara Pharmaceutical Journal, 1985)
Reductive cleavage of azo compounds with hydrazine hydrate and some new 1,3,4-thiadiazole derivatives.